2013
DOI: 10.4103/1755-6783.133685
|View full text |Cite
|
Sign up to set email alerts
|

A review of the national tuberculosis and leprosy control programme (ntblcp) of Nigeria: Challenges and prospects

Abstract: This review evaluates the National Tuberculosis and Leprosy Control Programme (NTBLCP) of Nigeria to identify challenges and prospects for reducing the burden of tuberculosis (TB) in Nigeria.TB remains the leading cause of death due to an infectious agent globally. Nigeria has the tenth largest burden of TB cases in the world. Rates of TB morbidity and mortality in Nigeria are spiralling despite expressions of political will to control TB and a clearly articulated NTBLCP policy. This is in contradistinction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 11 publications
3
38
0
Order By: Relevance
“…This study also found that government spending on TB control was inadequate, which is similar to evidence from several studies where donors, instead of governments, drive TB control efforts (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 87%
“…This study also found that government spending on TB control was inadequate, which is similar to evidence from several studies where donors, instead of governments, drive TB control efforts (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 87%
“…This has implication for the quality of service provided; for example, studies in Lesotho and Uganda identi ed poor sta ng situation as a major barrier to application of infection control guidelines and the effective implementation of measures such as screening for people with a cough, health education and timely sputum examination [22,24]. This has also been identi ed as a barrier to the successful implementation of DOTS in Nigeria [10,11]. There is, therefore, an urgent need to improve the sta ng situation in all the DOTS centres in order to increase e ciency and effectiveness of the services rendered and reduce heavy workload of the few available staff who are vulnerable to errors, fatigue and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…5 At this time, the country's response to TB was still evolving and health training programs had not fully incorporated DOTS into their curricula. It is therefore unlikely that most of the participants received adequate formal instruction on DOTS in the management of TB.…”
Section: Discussionmentioning
confidence: 99%
“…3 According to national tuberculosis and leprosy control program in Nigeria (NTBLCP), Nigeria is ranked among the 22 high burden countries in the world with predisposing factors including: overcrowding, poor nutrition, poverty, improper diagnosis and treatment and poor compliance. 4,5 In an attempt to stem TB epidemic, the World Health Organization (WHO) introduced the Directly Observed Treatment Short course (DOTS) strategy. 6 The DOTS strategy lays emphasis on close treatment monitoring of TB.…”
Section: Introductionmentioning
confidence: 99%